Managing service quality for competitive advantages in local financial institutions : a study on local commercial banks in Kuching, Sarawak - Hon,, Simon Lit Min (Universiti Malaysia Sarawak, (UNIMAS), 2002)
The current financial crisis coupled with government efforts to consolidate local financial institutions or local commercial banks towards 10 anchor banks under revised merger programme are forcing local commercial banks to improve their service quality as a significant source of competitive advantage in a competitive environment or marketplace